Isolation and Characterisation of L. plantarum O1 Producer of Plantaricin as Potential Starter Culture for the Biopreservation of Aquatic Food Products - Čanak, Iva; Markov, Ksenija; Melvan, Ena; Starčević, Antonio; Živković, Mattea; Zadravec, Manuela; Pleadin, Jelka; Jakopović, Željko; Kostelac, Deni; Frece, Jadranka (Food technology and biotechnology, 2018)
O1 was isolated from the gut of sea bream ( ) and identified with the API biochemical test and MALDI-TOF MS. This strain was further characterised according to the selection criteria for lactic acid bacteria as starter cultures for aquatic food production. O1 showed good antimicrobial activity against pathogenic test microorganisms. Further investigation confirmed it as the producer of the bacteriocin plantaricin. This strain also showed good growth at a wide range of temperatures (from 4 to 45 °C) and a wide range of pH (2-12), even in the presence of 3.5% NaCl. Its viability was also good after lyophilisation and in simulated gastric and small intestinal juice. The strain is a promising probiotic, and our further research will focus on its application in the biopreservation of fresh fish and shellfish.